Assessment of the environmental impact of acid mine drainage on surface water, stream sediments, and macrophytes using a battery of chemical and ecotoxicological indicators - Alvarenga, Paula (2021)
Mining activities at the Portuguese sector of the Iberian Pyrite Belt (IPB) have been responsible for the pollution of water, sediments, and biota, caused by the acid mine drainage (AMD) from the tailing deposits. The impact has been felt for years in the rivers and streams receiving AMD from the Aljustrel mine (SW sector of the IPB, Portugal), such as at the Água Forte stream, a tributary of the Roxo stream (Sado and Mira Hydrographic Region). To evaluate the extent of that environmental impact prior to the remediation actions, surface water, sediments, and the macrophyte Scirpus holoschoenus L. were sampled at the Água Forte and the Roxo streams, upstream and downstream from the confluence. The surface water and the sediments were extremely acidic at the Água Forte stream (pH ranges 2.22–2.92 for the water and 2.57–3.32 for the sediment), with high As, Cu, Pb, and Zn concentrations of 2.1, 120, 0.21, and 421 mg kg1, respectively, in the water, and 661, 1746, 539, and 1994 mg kg1, respectively, in the sediment, in the location closer to the mine. Two aquatic bioassays evidenced the high ecotoxicity of the Água Forte water at that site, with very low EC50 values for Vibrio fischeri luminescence inhibition (<3.1% v/v) and Daphnia magna 48-hour immobilization/mortality assays (<6.3% v/v). The impact of the AMD was also evident in the sediments of the Roxo stream, but not so marked in the water, with circa neutral pH and lower As, Cu, Pb, and Zn concentrations. Consistently, the ecotoxicological response was only felt in the sampling point closer to the confluence of the Água Forte with the Roxo stream, with an EC20 of 27.0% (v/v) towards the V. fischeri. One of the dominant and well adapted macrophytes, S. holoschoenus L., presented low bioaccumulation factors for Cu (0.04) and Zn (0.15) in their emerging parts, and very low concentrations for As and Pb, making this plant a potential candidate to be used in phytoremediation actions to treat and control AMD in the IPB